ANALISIS DAYA SAING EKSPOR KOPI INDONESIA DI PASAR DUNIA - Yuhendra, Alfis; Pebrian, Sispa (Jurnal Ilmiah Ekonomi, Manajemen dan Syariah, 2024)
This research was conducted to analyze the level of competitiveness of Indonesian coffee exports in the World Market. The data used is secondary time series data over a 10-year period (2013-2022). The object of this study is coffee with HS code: 090111. The analysis method uses quantitative methods used to analyze the level of competitiveness of Indonesian coffee commodity exports in the world market which includes: Self Sufficiency Ratio (SSR), Import Dependency Ratio (IDR), Revealed Comparative Advantage (RCA) and Index of Market Specialization (ISP). Based on the calculation of the average value, coffee in Indonesia has been able to meet domestic demand (SSR of 250.9%), but there is still import dependence (amounting to Rp 7.05%). The average RCA analysis score of 5.25 shows that Indonesia has a comparative advantage in coffee trade in the world market. However, Indonesia's comparative advantage still lags behind Colombia, Brazil, and Vietnam. Indonesia has a strong coffee export competitiveness which is indicated by an ISP value of 0.90